Clinicopathological Evaluation of Disseminated Metastases of Transmissible Venereal Tumor in a Spayed Bitch - Alkan, Hasan; Satilmis, Fatma; Alcigir, Mehmet Eray; Kivrak, Mehmet Bugra; Aydin, Ibrahim (Acta Scientiae Veterinariae, 2017)
Background: Although transmissible venereal tumor (TVT, transmissible venereal sarcoma, Sticker’s sarcoma) that affects dogs and other canids can be seen in many countries, it especially emerges in the countries which homeless dog population is very high. Female dogs are more susceptible than males. Transmissible venereal tumor is usually transmitted to genital organs during coitus and occasionally by social behavior such as sniffing and licking. The tumor is generally observed in the posterior part of the vagina. The tumor usually appears in various sizes, in the appearance of cauliflower, red and fragile. Metastases are rarely reported in cases with TVT. Metastases have been detected in lung, liver, tonsils, skin, lymph nodes, muscles, spleen. The diagnosis of transmissible venereal tumor is achived by considering the history of the animal, gross lesions, cytological examination and histopathology. Chemotherapy is frequently used in the treatment of TVT. In addition, radiotherapy, cryosurgery, surgical incision and immunotherapy are rarely applied for treatment. Chemical agents such as doxorubicin, vincristine sulfate, cyclophosphamide, methotrexate are preferred for chemotherapy. Case: Metastases to all mammary lobes, cervix uteri, neck, skin, gluteal muscles, the oropharyngeal region, and primary vaginal mass were described in spayed bitch, a 10-year old and mixed breed. The clinical examination manifested, fragile and hemorrhagic masses which resemble cauliflower in the vagina, neck, and inguinal region. Furthermore firm and multilobular masses in all mammary lobes, oropharyngeal region, and gluteal muscles of right leg were detected. Firstly, vaginal cytology was performed in order to confirm. In vaginal cytology, round to polyhedral shaped transmissible venereal tumor cells including cytoplasmic vacuoles and polychromatic nuclei were identified. Histopathologically, solid areas included oval- to round-shaped cells with prominent, hyperchromatic nuclei in all masses. Also, some of them comprised mitotic figures in their nuclei. In general, the tumor cells were separated by thin fibrous septa. Additionally, the cells were completely infiltrated to the mammary gland. In contrast, oropharyngeal and subdermal region of neck consisted more solid areas under the epidermis. There was lymphocyte infiltration at the periphery of the cells. For gluteal mass, TVT cells were confined in muscle bundles. Transmissible venereal tumor cases are often located in genital organs and their metastases are rarely encountered in comparison with other tumors. In this case report, metastases to cervical tissue, neck skin, oropharyngeal mucosa and gluteal muscles, mammary lobes are found. Discussion: When the sexual activity is high, the incidence of TVT increases. It especially develops in bitches in estrus. Breed, sex and age are not a cause of predisposition for TVT. Transmissible venereal tumors’ malignancy can increase in some cases, although TVT is known as a benign tumor. Prevalence of metastases was found fairly low in the studies. Metastases to mammary region, to subcutaneous region, to brain, to eye, to lung, to uterus, to ovary, to liver, to spleen have been reported. In conclusion, even if a bitch is acyclic, transmissible venereal tumor can be developed and thus the risk of its disseminated metastasis must be considered. Moreover, since the masses have not regresed for a long time, this situation may be related to severe immunosupression in the bitch.